An initial model for designing socially translucent systems for behavior change - Barreto, Mary L.; Szóstek, Agnieszka; Karapanos, Evangelos (My University, 2013)
Applications aiming at behavior change are gaining momentum within HCI. Much of that work has been built upon the idea of psychological empowerment. We report on a qualitative study that aimed at inquiring at an alternative path to behavior change through strengthening individuals' feelings of personal accountability. Two behavior-change-related scenarios were construed to evaluate how people perceive socially translucent systems aiding the process of behavior adaptation. We found that motivation to change is shaped by the access to information concerning one's behavior, by the type of provided feedback and the strength of the social ties accessing that information. Based on these results we propose an initial model defining possible approaches that can be considered when designing socially translucent systems supporting behavior change.
Keywords: Behavior change; Conceptual model; Social translucence